Nitrous oxide (N2O) and methane (CH4) in rivers and estuaries of northwestern Borneo - Aazani, Mujahid; Müller, Moritz; Bange, Hermann W.; Chun, Hock Sim; Bastian, Daniel; Kallert, Jennifer; Kock, Annette (Copernicus Publications on behalf of the European Geosciences Union, 2019)
Nitrous oxide (N2O) and methane (CH4) are atmospheric trace gases which play important roles in the climate and atmospheric chemistry of the Earth. However, little is known about their emissions from rivers and estuaries, which seem to contribute significantly to the atmospheric budget of both gases. To this end concentrations of N2O and CH4 were measured in the Rajang, Maludam, Sebuyau and Simunjan rivers draining peatland in northwestern (NW) Borneo during two campaigns in March and September 2017. The Rajang River was additionally sampled in August 2016 and the Samunsam and Sematan rivers were additionally sampled in March 2017. The Maludam, Sebuyau, and Simunjan rivers are typical “blackwater” rivers with very low pH (3.7–7.8), very high dissolved organic carbon (DOC) concentrations (235–4387 mmol L−1 ) and very low O2 concentrations (31–246 µmol L−1 ; i.e. 13 %–116 % O2 saturation). The spatial and temporal variability of N2O and CH4 concentrations (saturations) in the six rivers or estuaries was large and ranged from 2.0 nmol L−1 (28 %) to 41.4 nmol L−1 (570 %) and from 2.5 nmol L−1 (106 %) to 1372 nmol L−1 (57 459 %), respectively. We found no overall trends of N2O with O2 or NO−3 , NO− 2 or NH+ 4 , and there were no trends of CH4 with O2 or dissolved nutrients or DOC. N2O concentrations showed a positive linear correlation with rainfall. We conclude, therefore, that rainfall is the main factor determining the riverine N2O concentrations since N2O production or consumption in the blackwater rivers themselves seems to be low because of the low pH. CH4 concentrations were highest at salinity = 0 and most probably result from methanogenesis as part of the decomposition of organic matter under anoxic conditions. CH4 in the concentrations in the blackwater rivers showed an inverse relationship with rainfall. We suggest that CH4 oxidation in combination with an enhanced river flow after the rainfall events might be responsible for the decrease in the CH4 concentrations. The rivers and estuaries studied here were an overall net source of N2O and CH4 to the atmosphere. The total annual N2O and CH4 emissions were 1.09 Gg N2O yr−1 (0.7 Gg N yr−1 ) and 23.8 Gg CH4 yr−1 , respectively. This represents about 0.3 %– 0.7 % of the global annual riverine and estuarine N2O emissions and about 0.1 %–1 % of the global riverine and estuarine CH4 emissions. Therefore, we conclude that rivers and estuaries in NW Borneo – despite the fact their water area covers only 0.05 % of the global river/estuarine area – contribute significantly to global riverine and estuarine emissions of N2O and CH4.